Analysis of the sustainability of secondary cities in Africa: Evidence based on data from the Sarh Town in Southern Chad - Naringué, François Teadoum; Tob-Ro, N’Dilbé; Diaou, Elhadji Ibrahima; Haou, Ernest; Hetcheli, Follygan (Edelweiss Applied Science and Technology, 2025)
Although slower than that of metropolitan areas, the growth of secondary cities in Africa is nonetheless a major phenomenon influencing urban, socio-economic, and environmental dynamics. This research aims to assess the urban sustainability of Sarh based on the indicators of Sustainable Development Goal 11 (SDG 11). The methodology adopted is based on a mixed approach, combining documentary analysis, the use of demographic and spatial data, a survey of household heads, the calculation of SDG 11 indicators, interviews, and statistical analysis. The results reveal that the majority of SDG 11 indicators show significant negative deviations. Furthermore, the performance of these indicators is statistically associated with several socio-economic variables, including income, occupation, age, and residence status. Analysis of the correlation matrix highlights synergistic relationships between the indicators for SDG 1, SDG 6, SDG 8, SDG 9, and SDG 11. Finally, five main obstacles to urban development in Sarh were identified: weak governance (47.30%), urban poverty (15.06%), low citizen participation in urban planning and management (13.41%), insufficient infrastructure (12.23%), and social tensions (12%). This research highlights the critical need for effective urban policy strategies to address the challenges posed by the implementation of Sustainable Development Goal 11 (SDG 11) in secondary cities.